A Single‐Molecular AND Gate Operated with Two Orthogonal Switching Mechanisms. Issue 28 (17th May 2017) - Zhang, Na; Lo, Wai‐Yip; Jose, Anex; Cai, Zhengxu; Li, Lianwei; Yu, Luping
Abstract : Single‐molecular electronics is a potential solution to nanoscale electronic devices. While simple functional single‐molecule devices such as diodes, switches, and wires are well studied, complex single‐molecular systems with multiple functional units are rarely investigated. Here, a single‐molecule AND logic gate is constructed from a proton‐switchable edge‐on gated pyridinoparacyclophane unit with a light‐switchable diarylethene unit. The AND gate can be controlled orthogonally by light and protonation and produce desired electrical output at room temperature. The AND gate shows high conductivity when treated with UV light and in the neutral state, and low conductivity when treated either with visible light or acid. A conductance difference of 7.3 is observed for the switching from the highest conducting state to second‐highest conducting state and a conductance ratio of 94 is observed between the most and least conducting states. The orthogonality of the two stimuli is further demonstrated by UV–vis, NMR, and density function theory calculations. This is a demonstration of concept of constructing a complex single‐molecule electronic device from two coupled functional units. Abstract : A single‐molecule AND gate is constructed from two different switching mechanisms, the switch between conjugation to cross‐conjugation by light and the shift of conducting orbitals by protonation. The two switches are orthogonal and can be switched reversibly. The switching ratio between the highest and lowest conductance states is 94.